Real power loss diminution by rain drop optimization algorithm - Lenin Kanagasabai (International Journal of Advances in Applied Sciences, 2021)
In this work, the rain drop optimization (RDO) algorithm is projected to reduce power loss. Proceedings of rain drop have been imitated to model the RDO algorithm. The natural action of rain drop is flowing downwards from the peak and it may form small streams during the headway from the mountain or hill. As by gravitation principal rain drop flow as a stream as a river from the peak of mountains or hill then it reaches the sea as global optimum. Proposed rain drop optimization (RDO) algorithm evaluated in IEEE 30, bus test system. Power loss reduction, voltage deviation minimization, and voltage stability improvement have been achieved.